The Tools of argument: How the best lawyers think, argue, and win - Trachtman, Joel P. (CreateSpace Independent Publishing Platform North Charleston, South Carolina, 2013)
Joel Trachtman's book presents in plain and lucid terms the powerful tools of argument that have been honed through the ages in the discipline of law. If you are a law student or new lawyer, a business professional or a government official, this book will boost your analytical thinking, your foundational legal knowledge, and your confidence as you win arguments for your clients, your organizations or yourself.